1994
DOI: 10.1159/000246904
|View full text |Cite
|
Sign up to set email alerts
|

Eruptive Hamartomatous Clear-Cell Acanthomas

Abstract: This is a report on a 38-year-old female, suffering from over 100 solid papules arising on her legs, arms and trunk during the past 10 years. The histology shows the typical feature of clear-cell acanthoma (CCA). Extensive investigations did not reveal any extracutaneous abnormalities. This case is exceptional because of the high number of hamartomatous CCA which exceeds the maximal number of about 20 seen in multiple CCA so far and therefore is referred to as eruptive hamartomatous CCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
1
19
0
2
Order By: Relevance
“…This differs from previous reports, which state that the lesions usually appear slowly increasing in number over a period of 10 or more years. [1][2][3] It is also noteworthy that many of the lesions regressed, fact that has been previously reported. 16 Furthermore, the histopathological study suggested that the formation of clear cells rich in glycogen began close to nearby areas of intense spongiosis, which could support the existence of an underlying inflammatory condition.…”
Section: Case Reportsupporting
confidence: 72%
See 3 more Smart Citations
“…This differs from previous reports, which state that the lesions usually appear slowly increasing in number over a period of 10 or more years. [1][2][3] It is also noteworthy that many of the lesions regressed, fact that has been previously reported. 16 Furthermore, the histopathological study suggested that the formation of clear cells rich in glycogen began close to nearby areas of intense spongiosis, which could support the existence of an underlying inflammatory condition.…”
Section: Case Reportsupporting
confidence: 72%
“…5 Multiple disseminated eruptive CCA is a rare clinical variant that has been rarely reported. [1][2][3]6 It is characterized by the presence of more than 30 lesions from 1 to 10 mm in diameter that usually appear progressively, slowly increasing in number, over a period of years. 1 Lesions usually occur on the lower extremities of adult healthy women, although other locations, such as the trunk, wrist, and perineum have been described.…”
Section: Case Reportmentioning
confidence: 99%
See 2 more Smart Citations
“…The exact origin of CCA remains unclear. The epidermis, 12,16,20,21 acrosyringium 22 and hair follicles 23 have been proposed as possible sites of origin. Landry et al.…”
Section: Discussionmentioning
confidence: 99%